Applications and Implications from Epigallo Catechin Gallate (EGCG) in Green Tea - Fahmi, Aliyah; Syukur, Sumaryati; Chaidir, Zulkarnain; Melia, Sri (Journal of Midwifery and Nursing, 2024)
Epigallo catechin gallate (EGCG), a catechin bioactive component found in green tea, has been used widely as a popular beverage in Asian nations for centuries. According to a summary of five years’ worth of recent papers, EGCG has a wide range of positive benefits including anticancer, anti-cholesterol, cardiovascular agent, anti-virus, antioxidant, and adjuvant treatment agent. The purpose of this literature review is to get more knowledge on EGCG, the most prevalent catechin derivative found in green tea. A substance with significant antioxidant capabilities, EGCG has a wide range of applications. However, EGCG also has a number of drawbacks in addition to its benefits, such as low stability, poor absorption, and the requirement for a daily intake restriction because it acts as a pro-oxidant and can be harmful if consumed in excess. As a result, authors attempt to mitigate undesirable effects and discover a way to maximize EGCG benefits through additional study that serves as research material. Furthermore, we are becoming research subjects in order to against the negative effects of EGCG, such as how to use probiotics to boost the absorption of EGCG during digestion.